Faecal microbiota transplantation in recurrent Clostridium difficile infection: Recommendations from the French Group of Faecal microbiota Transplantation. Issue 3 (March 2016) - Sokol, Harry; Galperine, Tatiana; Kapel, Nathalie; Bourlioux, Pierre; Seksik, Philippe; Barbut, Frederic; Scanzi, Julien; Chast, François; Batista, Rui; Joly, Francisca; Joly, Anne-Christine; Collignon, Anne; et al.
Abstract: Faecal microbiota transplantation is effective for treating recurrent forms of Clostridium difficile infection and its use in this indication is recommended in the most recent European and North American guidelines. In this context, faecal microbiota transplantation is beginning to be performed in France in clinical practice, while the rules governing this procedure have been defined in France only for clinical trials. To unify, secure, and evaluate practice in this field in France, the French Group of Faecal microbiota Transplantation (FGFT) was created in October 2014 with the support of the French National Society of Gastroenterology, the French Infectious Disease Society, and the National Academy of Pharmacy. We present here the deliberations of this group regarding the use of faecal microbiota transplantation for recurrent Clostridium difficile infection. The issues addressed are the indications, therapeutic sequence, delivery procedures, donor selection, methods and conditions of specimen preparation, and traceability.